ANALISIS DAYA TARIK PRODUK RABBANI SEBAGAI FASHION DI LEMBAGA PENDIDIKAN AL-AZHAR JAMBI - Siyamsih, Dwi (Nomico, 2024)
This study aims to determine the factors that attract Al-Azhar Educational Institution to use Rabbani products as fashion clothing. Product attractiveness is a key to a product if it is to be chosen by consumers. The determinants of the attractiveness of Rabbani products are very useful to find out the background of interest in using these products. Rabbani is a type of product brand in which there are many kinds of Muslim products, one of the most famous is the instant hijab. Al-Azhar Institute is one of the users of Rabbani products used as fashion clothing.This research is a qualitative study with a descriptive analysis approach. The data in this study were collected through library research and field research techniques by means of interviews and observations. In this study there were 50 informants, all of whom were Al-Azhar teachers who used Rabbani products and the head of Al-Azhar institution as the main informant. The results of this study concluded that the background of Al-Azhar's use of Rabbani products was because previously Al-Azhar was looking for solutions to overcome the problems they experienced, namely making teachers' sports uniforms whose previous clothing designs were not the same. After looking for information on what products are suitable for overcoming these problems, Al-Azhar is interested in Rabbani products. While the characteristics of the attractiveness of Rabbani products until the Al-Azhar Institute uses Rabbani products as teacher uniforms until they are satisfied using these products include quality, design, and brand.